THE EFFECT OF GOOD CORPORATE GOVERNANCE IMPLEMENTATION OF FIRM VALUE WITH PROFIT MANAGEMENT AS MODERATING VARIABLES IN PROPERTY & REAL ESTATE COMPANIES IN INDONESIA STOCK EXCHANGE - Ulfa, Yustia (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to determine the effect of good corporate governance (institutional ownership, managerial ownership, independent board of commissioners and audit committees) on firm value in property & real estate sector companies on the Indonesia Stock Exchange. In addition, this study also aims to determine whether earnings management can be used as a moderating variable in the model. The research design carried out is a causal relationship research with a quantitative approach. The sample in this study were 26 property & real estate companies listed on the Indonesia Stock Exchange in 2012 to 2018. The type of data used in this study is secondary data. The technique of determining the sample using purposive sampling. And data analysis techniques using multiple linear regression analysis and interaction testing (moderating) conducted with the help of Eviews 9 software. The results in this study indicate that partially institutional ownership, independent boards of commissioners and audit committees have a positive and significant effect on firm value. As well as other results that show that earnings management is not a moderating variable in the effect of institutional ownership, managerial ownership, independent commissioners and audit committees on firm value in property & real estate sector companies listed on the Indonesia Stock Exchange